An objective-based evaluation of sport sponsorship in China - Shen, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction Modern marketing directors use a sole profit and loss assessment when selecting sponsorship proposals. Some proposals are evaluated by quantitative criteria such as media coverage value; others are assessed by comprehensive models such as the IEG Research has produced criteria and evaluation models on how corporations can benefit and achieve marketing objectives via sport sponsorships. However, the individual objectives and needs of sponsors should be prioritised. This study develops an objectivebased method to evaluate sport sponsorship within the Chinese context.